Evaluation of Right Ventricular Function and Dyssynchrony in a Dog Model of Acute Pulmonary Embolism: Diagnostic Utility and Reversibility - Morita, Tomoya; Nakamura, Kensuke; Osuga, Tatsuyuki; Kawamoto, Sei; Miki, Shingo; Takiguchi, Mitsuyoshi (Frontiers in Veterinary Science, 2022)
Background The diagnosis of acute pulmonary thromboembolism is challenging in dogs. Little has been reported on changes in echocardiographic indices in dogs with acute pulmonary thromboembolism. The objective of this study was to validate the relationship between echocardiographic indices and right heart catheterization variables in dogs with acute pulmonary embolism and to identify a useful echocardiographic index for diagnosing acute pulmonary embolism. Materials and Methods Six healthy laboratory beagles were included in the study. Echocardiography and right heart catheterization were performed in a dog model of acute pulmonary embolism produced by microsphere injection. Echocardiographic indices, including the right ventricular (RV) Tei index, RV longitudinal strain, and the dyssynchrony index using speckle tracking echocardiography, transmitral flow, and eccentricity index, were measured. Results The mean pulmonary arterial pressure increased (22.2 ± 1.2 mmHg) and the blood pressure decreased after microsphere injection. Although the mean pulmonary arterial pressure remained elevated, the blood pressure recovered 2 days after the microsphere injection. Most echocardiographic indices of RV function were significantly impaired following microsphere injection and recovered after 2 days. In contrast, the RV Tei index was significantly impaired after microsphere injection and the impairment persisted after 2 days. Multivariable analysis revealed that the RV Tei index was an independent echocardiographic predictor of pulmonary vascular resistance (β = 0.88, P < 0.001), and transmitral early diastolic wave was an independent predictor of the cardiac index (β = −0.86, P = 0.001). Conclusions The RV Tei index is a useful echocardiographic index for diagnosing acute pulmonary embolism. Ventricular interdependence may be an important factor causing low cardiac output in dogs with acute pulmonary embolism.